International Encyclopedia of the Social &Amp; Behavioral Sciences 2015
DOI: 10.1016/b978-0-08-097086-8.12138-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Anthropology

Abstract: Psychological anthropology is the anthropological study of people's beliefs, feelings, and motivations in cultural contexts. In the nineteenth and early twentieth centuries, questions about psychic unity and diversity were a central part of anthropology, not a separate subfield. Later, Freudian theory and the growth of the cognitive sciences inspired distinct schools within anthropology: one devoted to psychoanalytic studies of culture and personality and the other to formal models of cultural knowledge. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…(Andrew, 2021). Strauss (2015) in his writings defined psycho anthropology as "a subfield of anthropology devoted to the way cognition, emotion, and motivation are shaped in sociocultural settings and to the psychological factors that are important in culture learning and expression" (Strauss C. , 2015). Stich (1993) criticized folk psychology as a seriously mistaken theory and highlighted 4 elements (processes of behavior rise; belief and desire are common sense theory of the mind; a mature science that shows how the brain works; the existence of the intentional state of common-sense psychology) which showed that it was not true (Stich, 1993).…”
Section: Psychological Anthropologymentioning
confidence: 99%
“…(Andrew, 2021). Strauss (2015) in his writings defined psycho anthropology as "a subfield of anthropology devoted to the way cognition, emotion, and motivation are shaped in sociocultural settings and to the psychological factors that are important in culture learning and expression" (Strauss C. , 2015). Stich (1993) criticized folk psychology as a seriously mistaken theory and highlighted 4 elements (processes of behavior rise; belief and desire are common sense theory of the mind; a mature science that shows how the brain works; the existence of the intentional state of common-sense psychology) which showed that it was not true (Stich, 1993).…”
Section: Psychological Anthropologymentioning
confidence: 99%